Analisa Biaya Diferensial Dalam Pengambilan Keputusan Khusus (Studi Kasus Pada UMKM Alvine Di Kota Ambon) - Siahaya, Septina Louisa; Hasmawati, Hasmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Local Small and Medium Enterprise (UMKM) must always determine a superior strategy in marketing their products or services.This was also carried out by UMKM Alvine, one of the small businesses engaged in the bread business in Ambon City. The strategy undertaken is to provide special order facilities for customers. With a special order, UMKM Alvine need to apply the use of relevant cost to decide between accepting or rejecting the special order. In making decisions, differential cost analysis is used, which a different costs in a different situation or condition which will be compared with other conditions. The aim of this study was to determine the differential cost calculation applied to UMKM Alvine , as well as analyzing differential costs in relation to decision making in accepting or rejecting special orders from consumers , this is also become a consideration for UMKM Alvine in planning their future profits. The results of the study show that the Alvine UMKM decision to accept special orders from customers for chocolate bread products is justifiable. Because there is an additional income of Rp. 500.000 which is greater than the additional cost of Rp. 219.000. In addition, for contribution margin Rp. 13,211,000 which is higher than if the special order was rejected.